2021
DOI: 10.1242/dev.193227
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid production, regulation and containment through Zic1, Pitx2c and Cyp26c1 control cranial placode specification

Abstract: All paired sensory organs arise from a common precursor domain called the pre-placodal region (PPR). In Xenopus, Zic1 non-cell autonomously regulates PPR formation by activating retinoic acid (RA) production. Here we identified two Zic1 targets, the RA catabolizing enzyme Cyp26c1 and the transcription factor Pitx2c, expressed in the vicinity of the PPR as crucially required for maintaining low RA levels in a spatially restricted, PPR-adjacent domain. Morpholino- or CRISPR/Cas9-mediated Cyp26c1 knockdown abroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 81 publications
(113 reference statements)
0
16
0
Order By: Relevance
“…While there are several examples of cell-cell signaling being important in placode and neural crest induction (Begbie et al, 1999;Brugmann et al, 2004;Ahrens and Schlosser, 2005;Litsiou et al, 2005;Monsoro-Burq et al, 2005;Watanabe et al, 2015;Hintze et al, 2017;Plouhinec et al, 2017;reviewed in;Milet and Monsoro-Burq, 2012;Stuhlmiller and Garcia-Castro, 2012;Saint-Jeannet and Moody, 2014;Pla and Monsoro-Burq, 2018;Streit, 2018;Schlosser, 2021), there also is evidence for indirect signaling. For example, Dlx5 indirectly induces epidermal and PPR genes (McLarren et al, 2003) and Zic1 affects PPR gene expression at a distance by regulating retinoic acid signaling (Jaurena et al, 2015;Dubey et al, 2021). Since an alternate explanation is that the nβgal mRNA was selectively diluted in part of the clone, it will be important to confirm our lineage tracing data by grafting TFexpressing cells into an ectopic domain and observing reduced expression in the adjacent host tissue, as has been elegantly shown for dlx5 and six1 in Xenopus (Woda et al, 2003;Ahrens and Schlosser, 2005).…”
Section: Cell-to-cell Signaling Contributes To Domain Separation By N...mentioning
confidence: 58%
“…While there are several examples of cell-cell signaling being important in placode and neural crest induction (Begbie et al, 1999;Brugmann et al, 2004;Ahrens and Schlosser, 2005;Litsiou et al, 2005;Monsoro-Burq et al, 2005;Watanabe et al, 2015;Hintze et al, 2017;Plouhinec et al, 2017;reviewed in;Milet and Monsoro-Burq, 2012;Stuhlmiller and Garcia-Castro, 2012;Saint-Jeannet and Moody, 2014;Pla and Monsoro-Burq, 2018;Streit, 2018;Schlosser, 2021), there also is evidence for indirect signaling. For example, Dlx5 indirectly induces epidermal and PPR genes (McLarren et al, 2003) and Zic1 affects PPR gene expression at a distance by regulating retinoic acid signaling (Jaurena et al, 2015;Dubey et al, 2021). Since an alternate explanation is that the nβgal mRNA was selectively diluted in part of the clone, it will be important to confirm our lineage tracing data by grafting TFexpressing cells into an ectopic domain and observing reduced expression in the adjacent host tissue, as has been elegantly shown for dlx5 and six1 in Xenopus (Woda et al, 2003;Ahrens and Schlosser, 2005).…”
Section: Cell-to-cell Signaling Contributes To Domain Separation By N...mentioning
confidence: 58%
“…We further found that the RA-catabolizing enzyme, Cyp26c1, and the RA-dependent transcription factor Pitx2c expressed in a domain between ANP and PPR to be critical for PPR formation. 5 Interestingly, we also discovered that one of the RA metabolites generated by Cyp26c1, 4-oxo-RA, to be present during development at stages critical for the induction and specification of PPR. Consistent with this observation, previous reports have shown that 4-oxo-RA is capable of inducing signaling via RA receptors (RARs) to modulate the development of the anterior-posterior (A-P) axis in the embryo.…”
Section: Introductionmentioning
confidence: 87%
“…We next sought to verify that Zic1 is required for the expression of these genes. Using a well-characterized Zic1 morpholino antisense oligonucleotides (Zic1MO [3][4][5]15 ), we knocked down Zic1 in one half of the embryo at the two-cell stage and assessed the consequences by ISH at NF stage 15 (Figure 2). Our analysis revealed that Zic1 knockdown indeed disrupted the expression of these genes, providing further evidence that they are Zic1 targets.…”
Section: Patterning Genes Are Targets Of Zic1mentioning
confidence: 99%
See 2 more Smart Citations